Investigating Students’ Problems in Understanding English Reading Texts - anhar anhar (Lingedu: Journal of Linguistics and Education, 2026)
Understanding English reading texts is a critical skill for secondary‑school learners, yet many students encounter persistent difficulties that impede academic success. This study investigates the specific problems faced by Indonesian senior high‑school students when reading English narrative and expository texts. A mixed‑methods design was employed: a questionnaire (N = 210) identified the frequency of comprehension obstacles, and semi‑structured interviews (n = 12) explored underlying causes. Quantitative results revealed that limited vocabulary, insufficient inferencing skills, and low metacognitive awareness were the most prevalent issues (p < .01). Qualitative analysis highlighted gaps in prior knowledge, ineffective reading strategies, and limited exposure to authentic texts. Findings suggest that incorporating multimodal resources and mobile‑learning (M‑learning) platforms can alleviate these problems. Implications for curriculum design and teacher training are discussed.